2006
DOI: 10.1097/01.cpm.0000197344.91247.54
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Infections After Lung Cancer Resection

Abstract: The progress that has been made in patient selection, minimally invasive surgery, anesthesia (both in surgery and in the control of postoperative pain), and antibiotic treatments have substantially improved the morbility and mortality associated with the surgical treatment of bronchogenic carcinoma in recent years. Nevertheless, the rate of major complications after lung cancer resection is 2% to 22%, and the mortality rate is 2% to 7%. The most frequent complications after lung cancer resection are of respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 82 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…3,8,22 In this study, the no preop group was found to have significantly higher rates of abnormal leukocyte counts; however, given the lack of difference in radiographic findings and fever, this difference may be related to other complications, such as wound infection.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…3,8,22 In this study, the no preop group was found to have significantly higher rates of abnormal leukocyte counts; however, given the lack of difference in radiographic findings and fever, this difference may be related to other complications, such as wound infection.…”
Section: Discussionmentioning
confidence: 55%
“…[7][8][9][10] These large differences in reported incidences can be attributed to a number of differences in study characteristics, including the nature of the population, the degree of lung resection, antibiotic prophylaxis, defining criteria for PPC, and postoperative management (including pain control). 18 Atelectasis was the most frequent complication detectable via radiography.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations